Pengaruh Budaya Sekolah dan Iklim Kerja terhadap Kinerja Guru SMA Negeri di Kabupaten Sumbawa Barat - Mutya Gustina; Matin -; Yetty Supriati (Peneliti.net, 2019)
This study aims to determine the effect of school culture and work climate on performance. This research was conducted in public high schools using a survey method with multiple linear regression analysis applied in hypothesis testing and 60 samples selected by the sampling area. The findings of this study are (1) the positive direct influence of school culture on performance, (2) the positive direct influence of the work climate on performance, and (3) the positive direct influence of school culture on the work climate. Based on the findings in this study, it can be concluded that school culture and work climate have a direct effect on performance, and school culture has a very significant degree of influence compared to the work climate.